2020
DOI: 10.1002/adsc.201901582
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/NHC‐Catalyzed Enantioselective Cyclization of Pyridones and Pyrimidones with Tethered Alkenes

Abstract: Reported is a highly enantioselective Ni(0)‐catalyzed endo‐selective C−H annulation of 2‐ and 4‐pyridone, and 4‐pyrimidone with alkenes to provide drug‐relevant bicyclic heterocycle products. The use of a readily prepared chiral bulky NHC ligand (SIPE) for Ni catalyst and commercially available AlEt3 as co‐catalyst enhanced the practicality of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 69 publications
0
21
0
1
Order By: Relevance
“…The scope of this C−H annulation is very broad and encompasses various 2‐ and 4‐pyridones as well as uracils and thiopyridones to afford chiral N‐containing heterocycles in an attractive C−H functionalization protocol. A very similar study on the Ni‐NHC‐catalyzed pyridine C−H alkylation was reported [61b] …”
Section: Nickel‐bian‐nhc Complexesmentioning
confidence: 54%
“…The scope of this C−H annulation is very broad and encompasses various 2‐ and 4‐pyridones as well as uracils and thiopyridones to afford chiral N‐containing heterocycles in an attractive C−H functionalization protocol. A very similar study on the Ni‐NHC‐catalyzed pyridine C−H alkylation was reported [61b] …”
Section: Nickel‐bian‐nhc Complexesmentioning
confidence: 54%
“…For the synthesis of medium ring, a flexible large ring transition state would be involved, rendering the enantioselective control of such a reaction quite challenging 29 34 . By surveying a wide range of chiral carbenes, we found that bulky ANIPE, previously developed by Shi and Cramer groups 49 51 , was the optimal ligand (see the Supplementary Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…Until recent years, non-formyl C–H bonds were also able to be activated via nickel catalysis to form 7-membered rings (Fig. 1d ) 29 34 , while these examples were still limited to reactive C–H bonds such as heterocyclic and polyfluoro-aromatic C–H bonds, and moreover, only scattered substrates were reported with in general low to moderate yield and ee. In contrast, the activation of prevalent and unreactive aromatic C–H bonds towards 7-membered ring synthesis still remains an elusive challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They can undergo various selective transformations to afford a wide range of significant In this context, our group has developed a series of bulky C 2 -symmetric chiral N-heterocyclic carbenes (NHCs), 40 termed ANIPE-and SIPE-type ligands and applied to asymmetric nickel catalysis. [41][42][43][44][45][46][47][48] We recently disclosed the first general asymmetric arylboration of simple ketones to prepare chiral tertiary alcohols using Ni/NHC catalysis and a rare enantioselective η 2 -coordinating activation of ketones. [47,[49][50][51][52][53][54][55][56] Given the importance of chiral secondary alcohols, we became interested in developing asymmetric aldehyde addition of organoborons as a general and efficient approach to prepare chiral secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%